“Never Event” in surgery: Root-Cause Analysis (Revista Argentina de Cirugía, 2026)
At least half of the adverse events on hospitalized patients are associated with surgery.Root cause analysis (RCA) is a systematic way of analyzing these events to find their causes through a step-by-step review of the chronology of facts, identifying those that could have caused the event. An Ishikawa diagram (also called fishbone diagram) is a visual method for root cause analysis that allows the identification and categorization of all possible causes of an event.The goal is to answer what happened, why did it happen, and what can be done to prevent it from happening again. The ultimate goal is to improve healthcare processes by preventing the recurrence of the adverse event and prioritizing learning and improvement based on its analysis.Communicating the findings of the analysis and the measures to be implemented, discussing cases in morbidity and mortality meetings and continuous education of staff are the cornerstones for changing the culture towards one centered on safety and quality, replacing the “reactive” culture with a “proactive” culture, which considers events as an instrument for learning and continuousimprovement.
Keywords: root-cause analysis; error in surgery; safety culture